2014
DOI: 10.1158/2159-8290.cd-14-0362
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Is Critical for Pancreatic Tumor Growth and Progression in Tumors with p53 Alterations

Abstract: Pancreatic ductal adenocarcinoma is refractory to available therapies. We have previously shown that these tumors have elevated autophagy and inhibition of autophagy leads to decreased tumor growth. Using an autochthonous model of pancreatic cancer driven by oncogenic Kras and the stochastic LOH of p53, we demonstrate that while genetic ablation of autophagy in the pancreas leads to increased tumor initiation, these premalignant lesions are impaired in their ability to progress to invasive cancer, leading to p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
403
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 408 publications
(435 citation statements)
references
References 33 publications
25
403
1
Order By: Relevance
“…In vitro studies have shown that the survival of Rasdriven cancer cells requires autophagy and that gaining autophagy results in a marked increase in the survival of malignant cells under conditions of metabolic stress [28] . Inhibiting autophagy by deleting ATG5 prevents the progression of premalignant lesions to cancer in either a p53independent or p53 dependent manner [41,58] . Furthermore, deletion of ATG7 decreases the tumor growth rate and induces nonmalignant tumor formation.…”
Section: Autophagy As a Promoting Factor During Late Stagesmentioning
confidence: 99%
“…In vitro studies have shown that the survival of Rasdriven cancer cells requires autophagy and that gaining autophagy results in a marked increase in the survival of malignant cells under conditions of metabolic stress [28] . Inhibiting autophagy by deleting ATG5 prevents the progression of premalignant lesions to cancer in either a p53independent or p53 dependent manner [41,58] . Furthermore, deletion of ATG7 decreases the tumor growth rate and induces nonmalignant tumor formation.…”
Section: Autophagy As a Promoting Factor During Late Stagesmentioning
confidence: 99%
“…However, ablation of ATG5 was reported to either inhibit (13) or promote (16) pancreatitis. In addition, inhibition of autophagy can either accelerate the development of early malignant lesions in mice lacking the transformation-related protein 53 (p53) (19) or cause the death of established pancreatic cancer (20). The latter results gave rise to several ongoing clinical trials (clinicaltrials.gov numbers NCT01494155, NCT01978184, NCT01506973, NCT01128296, and NCT01273805) that intend to evaluate the impact of autophagy inhibitors on human pancreatic cancer.…”
mentioning
confidence: 99%
“…It has been shown that autophagy is elevated and required for de novo tumor growth and that inhibition of autophagy leads to robust tumor regression; 5,6 however, the status of p53 may determine the outcome of autophagy inhibition. 7,8 Despite the complexity of autophagy as a therapeutic target, these studies suggest that disabling the prosurvival autophagy machinery might represent a viable approach to promote cell death and reduce drug resistance in refractory cancers such as pancreatic cancer. 3,9 Because of their potential application as anticancer agents used alone or in combination with other cancer therapeutics, autophagy inhibitors have been actively pursued even though early inhibitors generally lack selectivity or target the lysosomal function.…”
Section: * S Supporting Informationmentioning
confidence: 99%